2022
DOI: 10.3889/oamjms.2022.9762
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of Bactericidal Permeability Increasing Protein (BPI) Polymorphysm rs1341023, rs5743507, Tumor Necrosis Factor Alpha (TNF-α) rs361525, rs1800629 with Neonatal Sepsis

Abstract: Background: Neonatal sepsis is a problem in the field of child health because the incidence is increasing every year and often ends in death. This study aimed to investigate the relationship between TNF-α and BPI gene polymorphisms with neonatal sepsis. Methods: PCR and sequencing examinations were performed on 60 DNA samples consisting of 30 samples of neonatal sepsis and 30 samples of non-neoptic sepsis. Furthermore, data in the form of DNA mutation tables were statistically processed by univariate, bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…We initially searched 1129 articles, of which 202 were in Chinese and 927 were in English. After a series of screening, 29 articles were finally included in the meta-analysis, including 4 articles [32][33][34][35] related to IL-1, 9 articles [34,[36][37][38][39][40][41][42][43] to IL-6, 2 articles [36,44] related to IL-8, 6 articles [38,43,[44][45][46][47] related to IL-10, and 8 articles [34,36,41,[48][49][50][51][52] related to TNF-α (see Figs 1-5). Basic information, genotype distribution, and quality of the included studies (NOS scores � 5 for all included studies) are shown in Table 1.…”
Section: General Situation and Quality Of Inclusion In The Studymentioning
confidence: 99%
See 1 more Smart Citation
“…We initially searched 1129 articles, of which 202 were in Chinese and 927 were in English. After a series of screening, 29 articles were finally included in the meta-analysis, including 4 articles [32][33][34][35] related to IL-1, 9 articles [34,[36][37][38][39][40][41][42][43] to IL-6, 2 articles [36,44] related to IL-8, 6 articles [38,43,[44][45][46][47] related to IL-10, and 8 articles [34,36,41,[48][49][50][51][52] related to TNF-α (see Figs 1-5). Basic information, genotype distribution, and quality of the included studies (NOS scores � 5 for all included studies) are shown in Table 1.…”
Section: General Situation and Quality Of Inclusion In The Studymentioning
confidence: 99%
“…Tatjana Varljen et al [8] found that TNF-α-308A allele may be a risk factor for earlyonset neonatal sepsis, while Lakshmi Srinivasan et al [28] did not find an association between tumor necrosis factor-308g /A polymorphism and sepsis. Therefore, we summarized relevant literature at home and abroad [34,36,41,[48][49][50][51][52] and found that the OR value of TNF-α-308G/A (rs1800629) polymorphism merged in the allele model was statistically significant (P = 0.016), indicating a significant increase in the risk of neonatal sepsis with the A allele (OR = 1.257, 95% CI: 1.044-1.513). The OR value merged in the recessive gene model was statistically significant (P = 0.009), indicating a significant increase in the risk of sepsis in newborns with the AA genotype (OR = 1.913, 95% CI: 1.179-3.104).…”
Section: Tumor Growth Factor-α (Tnf-α) Gene Polymorphismmentioning
confidence: 99%